ABOUT RELATIONSHIP BETWEEN RELIGION AND ART - A.J JAFAROV (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2021)
The concepts of religion and art have always been closely related. Both religion and art improve a person's spirituality, help him to enter the spiritual world, to feel the essence of being. Religion and art are one of the most important factors in the development of any civilization. Both religion and art are the main regulating part of the social structure of society, where the state of affairs varies depending on the nature of the religion to which it belongs. Art is also an instrument of human nature, and a creative person uses it to embody his inner world. Religious art occupies a high place in human life. The main purpose of religion is to make people understand that God exists, that God created you for a specific purpose, and that this purpose is beyond this limited world. The article examines the relationship between religion and art. Many of the links that have existed to date between religion and art have sometimes been mutually exclusive. Historically, some masters of the arts supported the religion, while others opposed it. And in our time, many creative people turn to religious themes and create brilliant examples of religious art. In the modern world, art and religion are often intertwined in different spheres. Both art and religion contribute to the development of human creativity. Both religion and art are capable of enlightening people. It can be concluded that religion and art have always directed their activities for the benefit of society.